Heritage risk index: A multi-criteria decision-making tool to prioritize municipal historic preservation projects - Ruiz-Jaramillo, Jonathan; Muñoz-González, Carmen María; Jayanes-Díaz, María D.; Jiménez-Morales, Eduardo; López-Osorio, José Manuel; Barrios-Pérez, Roberto; Rosa-Jiménez, Carlos (Elsevier & KeAi, 2020)
The current pressure on the built historical heritage requires a global evaluation to develop strategies for its preservation. A combined vision of the state of conservation of architectural heritage is essential to highlight the vulnerabilities of the structure from which harmonized measures can be proposed for its mitigation. This study proposes a multi-criteria analysis methodology that considers a qualitative and quantitative approach to organize the global conservation state of heritage buildings hierarchically. A global index can be determined on the basis of the generation of an interoperable data matrix by defining a set of indicators to assess different components of a building. This index describes the risk with respect to the stability, safety, and habitability of the building. This methodology aims to achieve the state of the building in an integral way by obtaining a simple and objective index that enables efficient comparison among different buildings. The application of this methodology to a historic area allows creating a hierarchical map of risk to stablish priorities for intervention and enable a sustainable and critical management and planning over the actions of maintenance, conservation, and restoration. In this way, a holistic vision of the complex reality of built heritage and the urban landscape is obtained to identify critical areas of priority intervention.
Keywords: Patrimonio histórico artístico; Historic city; State of conservation; Risk index; Intervention priority; Architectural heritage